Research on Clearance Elimination Control Based on Linearization - Tong Feng (IEEE, 2021)
The accuracy and operational stability of a turntable system can be reduced by the backlash problem that occurs in the reducer’s gear transmission system. To solve this problem, this work proposes a scheme in which two motors are used to eliminate the effects of backlash through a linearization process. By calculating and outputting two independent torques synchronously from the two servo motors to the system output shaft’s gears, a nonlinear system with backlash can be transformed into a linear system without backlash, thus making the resulting system easy to control. Experiments verify that the system will remain stable after the movement of the output shaft stops.